Analisis Penerapan Sistem Kredit Semester (SKS) Bagi Peserta Didik yang Memiliki Potensi Cerdas Istimewa dan Bakat Istimewa - Aiza Fitriana (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2021)
The government accommodates students who have different potentials of intelligence, talent and the demands of the times by issuing Law number 20 of 2003 which regulates the National Education System. This study aims to analyze the application of the Semester Credit System (SKS) for students who have special intelligent potential and special talents which is a case study at SMA Negeri 1 Lhokseumawe. The research method is based on a survey. Based on the results of the research, the results of the implementation of the Semester Credit System (SKS) program policies are managed starting from the application for operator permits, recruitment of new students, learning load, curriculum, assessment, graduation, supervision and evaluation. So it can be concluded that the implementation of the Semester Credit System (SKS) program policy on students who have special intelligent potential and special talents if managed properly can accommodate services for these unique students.